Rational composition engineering for high‐quality Pb–Sn photodetector toward sensitive near‐infrared digital imaging arrays - Huan Li; Yu Gao; Xin Hong; Kanghui Ke; Zilong Ye; Siwei Zhang; Kefei Shi; Zhuo Peng; Hao Yan; Man‐Chung Tang; Youwei Yao; Ben Zhong Tang; et al. (InfoMat)
Abstract Broadband photodetectors (PDs) capable of multi‐wavelength detection have garnered significant interest for applications in environmental monitoring, optical communication, spectral analysis, and imaging sensing. Low‐bandgap Pb–Sn hybrid perovskite photodetectors can extend the spectral response from the ultraviolet–visible (UV–vis) range to the near‐infrared (NIR) and reduce the toxicity associated with Pb2+. The strategic introduction of Sn2+ into Cs0.15FA0.85PbxSn1−xI3 (x = 1, 0.8, 0.6, 0.5, 0.4, 0.2, and 0) not only preserves the cubic crystal structure with conformal multigrain growth but also broadens the film's absorption spectrum from 800 to 1000 nm NIR region. This indicates a well‐controlled tunability of the Pb–Sn binary perovskite system. Specifically, the self‐powered photodetector with a device structure of ITO/NiOx/PTAA/Cs0.15FA0.85Pb0.5Sn0.5I3/PCBM/BCP/Ag has shown remarkable optoelectrical properties. It exhibits a high external quantum efficiency (EQE) of up to 80% across the spectrum from 300 to 1000 nm, a responsivity (R) exceeding 0.5 A/W, and high detectivity (D*) value of 1.04 × 1012 Jones at 910 nm and 3.38 × 1011 Jones at 1000 nm after weak attenuation. Intriguingly, the dark current of the Cs0.15FA0.85Pb0.5Sn0.5I3 device is four orders of magnitude lower than that of devices made with pristine Pb or Sn only, strongly correlating with its significantly increased built‐in potential and reduced trap density. Consequently, it demonstrates a −3 dB bandwidth of 2.23 × 104 Hz, fast rise and decay times of 61 and 30 μs, respectively, and a linear dynamic range (LDR) of 155 dB. Benefiting from its high sensitivity, a 5 × 5 PD array for NIR imaging and non‐invasive pulse detection for photoplethysmography applications has been successfully demonstrated, showcasing the prosperous potential of Pb–Sn hybrid perovskite in the NIR range.